Binding data mining to final business users of business intelligence systems - Azevedo, Ana (2012)
Since Lunh first used the term Business Intelligence (BI) in 1958, major transformations happened in the field of information systems and technologies, especially in the area of decision support systems. Nowadays, BI systems are widely used in organizations and their strategic importance is clearly recognized. The dissemination of data mining (DM) tools is increasing in the BI field, as well as the acknowledgement of the relevance of its usage in enterprise BI systems. One of the problems noted in the use of DM in the field of BI is related to the fact that DM models are, generally, too complex in order to be directly manipulated by business users; as opposite to other BI tools. The main contribution of this paper is a new DM language for BI conceived and implemented in the context of an Inductive Data Warehouse. The novelty is that this language is, by nature, user-friendly, iterative and interactive; it presents the same characteristics as the usual BI tools allowing business users to directly manipulate DM models and, allowing through this, the access to the potential value of these models with all the advantages that may arise.